Otimização inteligente da decomposição de elemento estruturante em morfologia matemática binária - Pillon, Paulo Eduardo (2014)
When working with binary images, mathematical morphology provides powerful tools for analyzing them. Along with genetic algorithms, it allows various computational tasks that are performed autonomously. In recent decades, the decomposition of structuring elements has been involved in the morphological operations used to reduce the degree of difficulty imposed by images of larger size implying in the efficiency of the hardware used for the processing of such images. For accelerating this process, this master's project uses MATLAB and Visual Studio as development tools, aiming at developing an efficient algorithm for decomposing the structuring element facilitating a possible hardware implementation with aim of decreasing the time waste in processing those images.